The effect of premixed bio-ceramic sealer versus standard sealer on post-obturation pain after single-visit endodontic therapy: a randomized clinical trial. - Showq A. Salem; Nora Agila; Ali Ashames Ali (African Journal of Advanced Pure and Applied Sciences, 2025)
Background: Postoperative pain frequently occurs following root canal treatment and is influenced by variables including pulp status, periapical condition, and the materials used for obturation. However, the specific impact of sealer type on post-obturation discomfort in vital mandibular premolars without periapical lesions has not been clearly established. Aim: This study aims to compare post-obturation pain following single-visit endodontic therapy using a bioceramic sealer versus AH Plus sealer in vital mandibular premolars tooth requiring of endodontic therapy without periapical pathosis. Materials and Methods: Forty vital mandibular premolars tooth (single root/canal) with Symptomatic Irreversible Pulpitis (SIP) were randomly allocated (1:1) to receive obturation using either a Bio-C sealer or an AH Plus sealer. All teeth were endodontically treated in a single visit utilized standardized instrumentation, irrigation, and obturation techniques. Post-obturation pain was documented with a 10-point Visual Analogue Scales (VAS) at 6, 24, 48, and 72 hours. Outcome data were statistically analyzed at a significance level of p<0.05. Results: The tested groups demonstrated a significant reduction in postoperative pain over time (p < 0.001). Pain was maximised at 6 hours (1.55±0.51 for AH Plus, 1.50±0.51 for Bio-C sealer) and subsequently declined after 24 hours (1.46 ± 1.96 for AH Plus, 1.21 ± 2.09 for Bio-C sealer), with no discomfort reported at 72 hours (0.00±0.00 for both sealers). There were no statistically significant differences identified between the groups at 6, 24 and 72 hours (p > 0.05). At 48 hours, AH plus group exhibited statistically significant higher pain scores (0.54 ± 0.96) than Bio-C group (0.03 ± 0.02) (P > 0.05). Overall, the Bio-C group reported lower pain scores throughout the observation period. Conclusion: The sealers evaluated in this study produced comparable levels of post-obturation pain, with no observable differences in either the intensity or incidence of pain experienced following single-visit treatments. This randomised clinical trial demonstrated that the pain intensity post-obturation starting from 6 hours and declined rapidly with time, irrespective to the type of sealer used.